Gatchaman : Galactor - Orlando, Steve (Comic book writer) (Mad Cave Studios, 2024)
"Galactor is under siege by a threat from within! After a secret attempt on his life, Berg Katse sets about to uncover a conspiracy within Galactor, born of their earliest days. Galactor's leader goes undercover to hunt, identify, and ruthlessly dispense with a revolution growing within Galactor's ranks. The masked villain Berg Katse must root out a conspiracy within Galactor, the sinister organization that plagues Science Ninja Team Gatchaman." --